2021
DOI: 10.3390/cosmetics8010008
|View full text |Cite
|
Sign up to set email alerts
|

Seaweeds Compounds: An Ecosustainable Source of Cosmetic Ingredients?

Abstract: Seaweed-based cosmetics are being gradually used by consumers as a substitute of synthetic equivalent products. These seaweed-based products normally contain purified compounds or extracts with several compounds. Several seaweeds’ molecules already demonstrated a high potential as a cosmetic active ingredient (such as, mycosporine-like amino acids, fucoidan, pigments, phenolic compounds) or as a key element for the products consistency (agar, alginate, carrageenan). Moreover, seaweeds’ compounds present import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 219 publications
(405 reference statements)
1
49
0
Order By: Relevance
“…presented some similarities in their FA profiles, with 16:0 and 18:1( n -7+ n -9) displaying the highest relative abundances in the total pool of FAs recorded in both locations. This finding is in line with previous studies [ 51 , 52 , 53 ]. Our results on the profiling of unsaturated FAs (MUFA+PUFA) are fully aligned with those reported by Herbreteau et al [ 54 ], who reported the FA composition of five species of seaweeds and verified that unsaturated FAs accounted for more than 50% of the total pool of FAs, with this proportion reaching up to 75% for Fucus sp.…”
Section: Discussionsupporting
confidence: 94%
“…presented some similarities in their FA profiles, with 16:0 and 18:1( n -7+ n -9) displaying the highest relative abundances in the total pool of FAs recorded in both locations. This finding is in line with previous studies [ 51 , 52 , 53 ]. Our results on the profiling of unsaturated FAs (MUFA+PUFA) are fully aligned with those reported by Herbreteau et al [ 54 ], who reported the FA composition of five species of seaweeds and verified that unsaturated FAs accounted for more than 50% of the total pool of FAs, with this proportion reaching up to 75% for Fucus sp.…”
Section: Discussionsupporting
confidence: 94%
“…Many concerns are emerging for all chemicals: In some cases, safety data are lacking for synthetic ingredients and they might cause hypersensitivity reactions, anaphylactic reactions, lethal poisonings or long time effects to users. Systematic monitoring of these substances can be made by testing their genetic toxicity, phototoxicity, photogenotoxicity, toxicokinetics, and carcinogenicity and new studies might reveal different toxicity data [38][39][40][41]. Furthermore, the daily use of many cosmetic products leads to continuous exposure to different chemicals.…”
Section: Lipids For Cosmetic Usesmentioning
confidence: 99%
“…Europe is still an emerging industry with only a small number of commercial seaweed farms [92]. Seaweed harvesting or culturing intended for cosmeceutical uses only represent a minor percentage of total production [93]; however, clearly, it is a non-stop growing industry, which indeed faces new challenges such as the need for adopting sustainable exploitation procedures managed under maximum sustainable yield plans within a circular economy approach, contributing to a resilient and sustainable marine and maritime sector [94]. Different species of macroalgae such as Gracilaria spp.…”
Section: Sustainable Sourcing Of Cosmeceutical Ingredients From Aquatic Organismsmentioning
confidence: 99%